SISTEM INFORMASI E-ARSIP PERSURATAN BERBASIS WEBSITE PADA KANTOR DESA GATTARENG - Ita Sulfiani; Farida; Nurwahid Syam (Journal System Information And Computer, 2024)
Abstrak – This study aims: (1) to design a website-based correspondence E-Archive information system at the Gattareng village office (2) to implement a website-based E-Archive correspondence information system at the Gattareng village office (3) to find out how users respond to the E-information system -Web-based correspondence archive at the Gattareng village office. the development of science in the field of technology and information and communication (ICT) has a considerable influence on organizational activities, especially related to archives, while the archive system at the village office in Gattareng village is still being carried out by first opening a collection of archives one by one. , so it is less efficient to store archival data in hardcopy form for fear of being lost, damaged or scattered. Based on these problems, the mailing E-Archive system is a solution where the E-Archive system is useful for storing archives in the form of files that can be accessed by software to support various activities in order to achieve organizational goals. This system uses the PHP programming language and MySQL database so that the system is no longer in the form of hardcopy but is already in the form of a scanned file which will be stored to make it easier to search so that archives entered several years ago are not damaged and are easy to find. The research method used in designing a website-based E-Archive correspondence information system at the Gattareng village office uses the waterfall approach or the waterfall method, where this method has the stages of analysis, design, coding, testing, implementation and maintenance. Based on the results of the study, it shows that: (1) a website-based e-archive information system for correspondence is designed and used based on problems that occur in archiving letters at the village office and the design of the system and built using the php programming language using the MySQL database as the database and tested using black box method (2) the results of the implementation of the website-based E-Archive correspondence information system at the Gattareng village office, namely helping village office staff and facilitating the preparation of reports (3) user satisfaction with the website-based E-Archive correspondence information system at the Gattareng village office of 95.56% or very positive.